IMPROVING STUDENTS’ VOCABULARY THROUGH DISPLAY TABLE GAME - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2022)
The purpose of this research is to prove whether display table games are effective or not in improving students’ vocabulary at SMP Negeri 1 Ratahan. This study is quantitative, with a pre-experimental design and a one-group pretest and post-test design. An objective test was used to collect data for this study. The findings of this study revealed that students' post-test scores were higher than their pre-test scores. The mean of the post-test was 73, while the mean of the pre-test was 61.5. It means that using display table games in teaching vocabulary is effective in increasing students’ vocabulary.